Simple diagnosis of STAT1 gain-of-function alleles in patients with chronic mucocutaneous candidiasis. Issue 4 (16th December 2013) - Mizoguchi, Yoko; Tsumura, Miyuki; Okada, Satoshi; Hirata, Osamu; Minegishi, Shizuko; Imai, Kohsuke; Hyakuna, Nobuyuki; Muramatsu, Hideki; Kojima, Seiji; Ozaki, Yusuke; Imai, Takehide; Takeda, Sachiyo; et al.
Abstract : Flow cytometry-based diagnostic technique should facilitate the diagnosis of patients with CMCD, with gain-of-function STAT1 mutations. Abstract: CMCD is a rare congenital disorder characterized by persistent or recurrent skin, nail, and mucosal membrane infections caused by Candida albicans . Heterozygous GOF STAT1 mutations have been shown to confer AD CMCD as a result of impaired dephosphorylation of STAT1. We aimed to identify and characterize STAT1 mutations in CMCD patients and to develop a simple diagnostic assay of CMCD. Genetic analysis of STAT1 was performed in patients and their relatives. The mutations identified were characterized by immunoblot and reporter assay using transient gene expression experiments. Patients' leukocytes are investigated by flow cytometry and immunoblot. Six GOF mutations were identified, three of which are reported for the first time, that affect the CCD and DBD of STAT1 in two sporadic and four multiplex cases in 10 CMCD patients from Japan. Two of the 10 patients presented with clinical symptoms atypical to CMCD, including other fungal and viral infections, and three patients developed bronchiectasis. Immunoblot analyses of patients' leukocytes showed abnormally high levels of pSTAT1 following IFN-γ stimulation. Based on this finding, we performed a flow cytometry-based functional analysis of STAT1 GOF alleles using IFN-γ stimulation and the tyrosine kinase inhibitor, staurosporine. The higher levels of pSTAT1 observed in primary CD14 + cells from patients compared with control cells persisted and were amplified by the presence of staurosporine. We developed a flow cytometry-based STAT1 functional screening method that would greatly facilitate the diagnosis of CMCD patients with GOF STAT1 mutations.